2012
DOI: 10.1017/s1751731111002680
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal mucin composition and mucosal morphology by dietary phytogenic inclusion level in broilers

Abstract: The effect of a dietary phytogenic feed additive (PFA) inclusion level in mucin monosaccharide composition, mucosal morphometry and mucus histochemistry along the broiler intestinal tract was studied. Cobb male broilers (n 5 525) were allocated into five experimental treatments that, depending on the type of addition in the basal diet (BD), were labeled as follows: C (BD based on maize-soybean meal with no other additions), E1 (80 mg PFA/kg BD), E2 (125 mg PFA/kg BD), E3 (250 mg PFA/kg of BD) and A (2.5 mg avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
7
25
2
4
Order By: Relevance
“…The observed increase in the mucus layer thickness could be considered as benefi cial and could indicate a dietary sage protective role. Our results are similar to the work of Tsirtsikos et al [11] who observed a linear increase of the duodenal mucus layer thickness with increasing phytogenic feed additive dietary levels (carvacrol, anethol and limonene at concentrations of 115 g.kg -1 feed additive) in broiler chickens. According to Jamroz et al [12], in groups of chickens fed with plant extract mixture (containing carvacrol, cinnamaldehyde and capsaicin) showed an increased release of large amounts of mucus and the creation of a thick layer of mucus on the wall of the jejunum.…”
Section: Discussionsupporting
confidence: 92%
“…The observed increase in the mucus layer thickness could be considered as benefi cial and could indicate a dietary sage protective role. Our results are similar to the work of Tsirtsikos et al [11] who observed a linear increase of the duodenal mucus layer thickness with increasing phytogenic feed additive dietary levels (carvacrol, anethol and limonene at concentrations of 115 g.kg -1 feed additive) in broiler chickens. According to Jamroz et al [12], in groups of chickens fed with plant extract mixture (containing carvacrol, cinnamaldehyde and capsaicin) showed an increased release of large amounts of mucus and the creation of a thick layer of mucus on the wall of the jejunum.…”
Section: Discussionsupporting
confidence: 92%
“…The intestinal crypts of the broiler chickens fed both the C and the HI-based diets in the current research showed greater mucin staining intensity in the base compared with the other crypt fragments. A decreased stain in the tip represents the physiological condition in the intestinal crypts, as previously reported [10,16,17,65]. On the contrary, the intestinal villi showed unaffected mucin staining among the villus fragments.…”
Section: Discussionsupporting
confidence: 79%
“…Bacterial colonization and proliferation has been reported to have a key role in determining the mucin composition, both by the synthesis of mucin-specific glycosidases, glycosulfatases and proteases [7,8] and the modulation of mucin gene expression [9]. There is also evidence that several feed substances may widely affect the complex, delicate relationship existing between the gut microbiota and mucin dynamics in poultry, either by directly modifying the intestinal mucin composition [10,11], or indirectly by modulating the intestinal microbial population [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The present data are in harmony with those obtained by Geyra et al (2001) indicated that zinc repaired intestinal injury by reducing the apoptotic index of ileal epithelial cells, enhancing villus height and the villus-height/crypt-crypt development is essential to increase cell renewal rate and maturation in the gut. The increase in crypt depth of chicken supplemented with different levels of nano zinc/kg might provide more surface area for nutrient absorption by increasing enterocyte proliferation and intestinal mucin secretion because mucinproducing goblet cells are present mainly in the crypts (Tsirtsikos et al, 2012). The villous height/crypt ratio most widely used as a marker of mucosal integrity and intestinal function (Clarke et al, 2006;Lamb-Rosteski et al, 2008).…”
Section: 6antioxidant Enzyme Activitymentioning
confidence: 99%